PENGGUNAAN METODE RESITASI DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MAN GANDEKAN BANTUL - Cahyaningsih, Miftahul (Universitas Ahmad Dahlan, 2011)
This study aims to find out the differences in mathematics learning outcomes of students who use the method of recitation by using the drill method in class XI student IPS MAN Gandekan Bantul in second Semester Academic Year 2010/2011. The populations in this study are all students class XI IPS MAN Gandekan Bantul in second Semester Academic Year 2010/2011 which consists of 3 classes. The sampling technique used random cluster sampling technique and the sample in this study was taken two classes, namely class XI IPS 2 as the experimental class and class XI IPS 1 as the control class. Data collecting technique is documentation method to determine the ability of students, the test method to determine mathematics student learning outcomes. To test the validity of test instruments used, distinguishing features and reliability. Data analysis used the t-test two parties and one party t-test. Results showed no differences between the results of learning mathematics using method of recitation and drill method in class XI student of second Semester MAN IPS Gandekan Bantul School Year 2010/2011, is shown from the results of the t-test with the two parties t_count (5.59139)> t_tabel (2.40155) at 53 degrees of freedom significant level of 5%. The results also showed that the use of the recitation method is more effective than the use of the drill method in improving students mathematics learning outcomes, shown in the t-test results of one party with t_count (5.59139)> t_tabel (0.16055) at 53 degrees of freedom significant level 5 %.